2013
DOI: 10.1002/2013gc004997
|View full text |Cite
|
Sign up to set email alerts
|

Is the electrical conductivity of the northwestern Pacific upper mantle normal?

Abstract: [1] The Normal Oceanic Mantle project, based on ocean bottom geophysical observations, has been underway since 2010 to investigate the physical state of the oceanic lithosphere and asthenosphere. We have conducted electromagnetic surveys on old (130 Ma) seafloor in the northwestern Pacific region, where no active tectonic processes have been identified, in order to image the electrical conductivity structure beneath the region. So far, data have been collected at four sites through a pilot survey conducted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…The positions given in italicized characters are the representative positions for each site. Water depths at each site were retrieved from the up-to-date compilation of available MBES data, and the values for some sites are therefore slightly different from those previously reported by Baba et al (2010Baba et al ( , 2013a where r is the observed position and T is the period. The responses were estimated for each OBEM site using a bounded influence algorithm (Chave and Thomson 2004).…”
Section: Magnetotelluric Analysismentioning
confidence: 93%
See 4 more Smart Citations
“…The positions given in italicized characters are the representative positions for each site. Water depths at each site were retrieved from the up-to-date compilation of available MBES data, and the values for some sites are therefore slightly different from those previously reported by Baba et al (2010Baba et al ( , 2013a where r is the observed position and T is the period. The responses were estimated for each OBEM site using a bounded influence algorithm (Chave and Thomson 2004).…”
Section: Magnetotelluric Analysismentioning
confidence: 93%
“…This phenomenon is smaller for Area B, which is more distant from the coastlines; therefore, the coast effect is likely a possible cause. In fact, our previous study showed that splitting in the responses for Area A is partly explained by the topography, including coastlines (Baba et al 2013a). However, for Area A, the splitting tends to be slightly more significant at the western sites, NM01, NM02, and NM04 ( Fig.…”
Section: Magnetotelluric Analysismentioning
confidence: 96%
See 3 more Smart Citations